KOMUNIKASI DAKWAH DALAM PEMBINAAN AKHLAK SISWA/SISWI SMK PERTAMBANGAN BULI KABUPATEN HALMAHERA TIMUR MALUT - Laode Ilman; Sandi Safrudin; Fikalisman Husain; Akmal Yusup; Nazilah Isnainiyah Irwan; La Ode Ilman; Fauji Ilyas (Journal of Islamic Science Community, 2025)
SMKS Pertambangan Buli is an educational institution located in North Maluku, focusing on vocational education. However, the students of SMK PERTAMBANGAN BULI face several issues, such as engaging in romantic relationships within the school environment, displaying inappropriate behavior toward the opposite sex and even mocking, insulting, or bullying one another. This research aims to convey Islamic da'wah messages in fostering the moral character (akhlaq) of students at SMK PERTAMBANGAN BULI. The findings of this study indicate that Da'wah Communication, in the aspect of character development, can be effectively implemented among the students through proper guidance and exemplary behavior. This approach helps to create a more inclusive and sustainable school environment.